Al-Ghazali’s Concept of Hifdzul Lisan Regarding the Issue of Hate Speech - Shalahuddin, Henri; Zulfa, Santi; Indallah, Sayyid Muhammad; Ilaini, Wafiq Nur; Da’i, Rahmat Ardi Nur Rifa (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2025)
Hate speech has become a significant problem in the modern era, causing social tensions and negative impacts on individuals’ mental health. The spread of hate speech through social media and digital platforms exacerbates polarization and conflicts between groups, demanding effective solutions to address these social impacts. This research aims to explain the concept of hifdzul lisan according to Al-Ghazali and examine its application as a solution to the problem of hate speech. The research method used is descriptive-analytical with an Islamic psychology approach, utilizing primary and secondary sources to explore the topic. The findings indicate that hate speech is a harmful societal issue that Al-Ghazali’s concept of hifdzul lisan emphasizes ethical speech and avoiding harmful words, and that applying the principles of hifdzul lisan can serve as a solution to mitigate and address hate speech by promoting more constructive and respectful communication. This study provides an academic contribution by integrating Al-Ghazali’s concept of Hifdzul Lisan into modern communication ethics to examine the phenomenon of hate speech, while socially contributing by raising public awareness to safeguard speech in any spaces for the sake of fostering tolerance and harmony.